Thomas D. Clark of Kentucky : an uncommon life in the Commonwealth - Kleber, John E., 1941- (Lexington : The University Press of Kentucky, 2015)
Special numbered leatherbound edition, signed by Dr. Clark! By the flip of a coin, Thomas Dionysius Clark became intertwined in the vast history of Kentucky. In 1928, Clark received scholarships to both the University of Cincinnati and to the University of Kentucky. Kentucky won the coin toss and the claim to one of the South's eminent historians. In 1990, when the Kentucky General Assembly honored Clark by declaring him Kentucky's Historian Laureate for life, Governor Brereton Jones described Clark as ""Kentucky's greatest treasure."" Historian, advocate, educator, preservationist, publisher
Cover; Half-title; Title; Copyright; Contents; Photo credits; Foreword; Preface; PART I. THE LIFE; Biography; PART II. THE HISTORIAN; Kentucky Historian; Local Historian; Southern Historian; PART III. THE ADVOCATE; Agrarian; Education Advocate; Kentuckian; Preservationist; Publisher; PART IV. THE FRIEND; Colleague; Southern Writer; Friend; Inspirer; Mentor; PART V. THE WORKS; Bibliographic Essay; Contributors; Index.
Print version record.
eBooks on EBSCOhost
Keywords: Clark, Thomas Dionysius, -- 1903-2005.; Clark, Thomas Dionysius, -- 1903-2005; Historians -- Kentucky -- Biography; Kentucky -- Biography; Kentucky -- Historiography; Kentucky -- Biographies; Kentucky -- Historiographie; HISTORY -- United States -- State & Local -- General; HISTORY -- General; Historians; Historiography; Kentucky; Biographies